2015
DOI: 10.3390/s150100715
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of WiFi, Smartphone Sensors and Landmarks Using the Kalman Filter for Indoor Localization

Abstract: Location-based services (LBS) have attracted a great deal of attention recently. Outdoor localization can be solved by the GPS technique, but how to accurately and efficiently localize pedestrians in indoor environments is still a challenging problem. Recent techniques based on WiFi or pedestrian dead reckoning (PDR) have several limiting problems, such as the variation of WiFi signals and the drift of PDR. An auxiliary tool for indoor localization is landmarks, which can be easily identified based on specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
240
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(243 citation statements)
references
References 25 publications
0
240
0
3
Order By: Relevance
“…Using location information, a more specific and detailed location-based classifier can be applied. There are well-known ways to obtain location information indoors [18,19] and outdoors [20,21]. In this study, however, the location information is not collected from the system and derived from the type of activities.…”
Section: Classifiermentioning
confidence: 99%
“…Using location information, a more specific and detailed location-based classifier can be applied. There are well-known ways to obtain location information indoors [18,19] and outdoors [20,21]. In this study, however, the location information is not collected from the system and derived from the type of activities.…”
Section: Classifiermentioning
confidence: 99%
“…There have been many studies on sensor based positioning systems in the indoor environment [19,20,25]. [19] proposed a novel data fusion framework by using an extended Kalman filter to integrate WiFi localization with pedestrian dead reckoning.…”
Section: Sensor Based Positioning Systemmentioning
confidence: 99%
“…There are several step length estimation methods that have been proposed for different applications in the past [21][22][23]. A comparison of several popular methods has revealed that the one proposed by Weinberg et al is best suited for a waist-mounted IMU [16,26].…”
Section: Knowledge-based Sle Algorithm Based On Fuzzy Logicmentioning
confidence: 99%